2010
DOI: 10.1074/jbc.m109.087718
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Peroxisome Proliferator-activated Receptor-γ Contributes to Phenotypic Modulation of Vascular Smooth Muscle Cells during Hypertension

Abstract: The phenotypic modulation of vascular smooth muscle cells (VSMCs) plays a pivotal role in hypertension-induced vascular changes including vascular remodeling. The precise mechanisms underlying VSMC phenotypic modulation remain elusive. Here we test the role of peroxisome proliferator-activated receptor (PPAR)-␥ in the VSMC phenotypic modulation during hypertension. Both spontaneously hypertensive rat (SHR) aortas and SHR-derived VSMCs exhibited reduced PPAR-␥ expression and excessive VSMC phenotypic modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…At the same time, the expression of smooth musclespecific contractile markers, such as SM α-actin and SM22α, is decreased [18]. This dedifferentiated phenotype contributes to the pathogenesis of many cardiovascular disorders, including atherosclerosis, restenosis after angioplasty or bypass, and hypertension [19][20][21]. It is well established that PDGF-BB is a key mediator of VSMC phenotypic switching [22].…”
Section: Discussionmentioning
confidence: 97%
“…At the same time, the expression of smooth musclespecific contractile markers, such as SM α-actin and SM22α, is decreased [18]. This dedifferentiated phenotype contributes to the pathogenesis of many cardiovascular disorders, including atherosclerosis, restenosis after angioplasty or bypass, and hypertension [19][20][21]. It is well established that PDGF-BB is a key mediator of VSMC phenotypic switching [22].…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that the PI 3 K/AKT signaling pathway is closely related to PPARγ (Honda, Matsuura, Fukushima, et al, 2009;Zhang, Xie, Wang, et al, 2010). PI 3 K is an intracellular phosphatidylinositol kinase that is required for either insulin-stimulated uptake of glucose or GLUT 4 translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Basal levels of VSMC migration were different between the 2 strains (data not shown), in accordance with previous reports. 39 Previous studies have associated increased ROS levels 40,41 and activation of c-Src 42 with VSMC migration. However, there are no data showing that testosterone induces VSMC migration.…”
Section: Discussionmentioning
confidence: 99%